Contribution by the Latin American and Caribbean countries to the V General Conference (SELA CaracasVE, 1993)
Presents the Latin American and Caribbean position for the V UNIDO General Conference to be held from 6 to 10 December 1993 in Yaounde, Cameroon.
DC